A relation between high-density-lipoprotein cholesterol and bile cholesterol saturation. Issue 6303 (21st November 1981) - Thornton, J R; Heaton, K W; Macfarlane, D G
Abstract : The association of cholesterol gall stones with coronary artery disease is controversial. To investigate this possible relation at the biochemical level, bile cholesterol saturation and the plasma concentrations of triglycerides, total cholesterol, and high-density-lipoprotein cholesterol (HDL cholesterol) were measured in 25 healthy, middle-aged women. Bile cholesterol saturation index was negatively correlated with HDL cholesterol. It was positively correlated with plasma triglycerides and with total cholesterol minus HDL cholesterol. These findings provide a biochemical basis for a positive association in women between cholesterol gall stones and coronary artery disease.